Optimalisasi Pemberdayaan dan Pengoranisasian Sumber Daya Manusia untuk Meningkatkan Mutu Lembaga Pendidikan Islam - Pepen Supendi; Ali Zainudin; Afni Fauziyah Saepulloh (Tadbir: Jurnal Manajemen Dakwah, 2019)
This study explores organizational values ​​in education and how they are important to achieve the goals of educational institutions. To ensure that instructional objectives are fully achieved, educational institutions must have a structure. The actions of the principal showing excessive (authoritarian) power can be avoided with the organization, and the work environment can be more lively because of the responsible involvement of all parties involved. In Islam, trust should be given to those who have rights, i.e. those with management and intellectual abilities, and these people should be mandated in certain positions according to their qualifications.